Oral Health Attitudes and Behavior among a Group of Turkish Dental Students - Peker, Ilkay; Alkurt, Meryem Toraman (European Journal of Dentistry, 2009)
Objectives: The purpose of this study was to evaluate self-reported oral health attitude and behavior among a group of Turkish dental students and to compare differences in oral health attitudes between years of study and gender.Methods: This study included 267 (153 female, 114 male) dental students. A modified English version of Hiroshima University Dental-Behavioral Inventory (HU-DBI) which consists of twenty-eight dichotomous responses (yes-no) was used.Results: Totally 141 preclinical (1, 2 and 3rd years of study) and 126 clinical students (4 and 5th years of study) who were mean age of 21.16 participated in the study. Statistically significant differences were found between years of study for brushing each of teeth carefully, cleaning the teeth well without using toothpaste, using a toothbrush which has hard bristles and for having had their dentist tell that they brush very well. There were statistically significant differences between females and males for using a toothbrush which has hard bristles and using tooth floss regularly. Statistically significant differences were found for brushing each of the teeth carefully and using mouth wash on regular basis between smokers and non-smokers.Conclusions: This study confirmed that oral and dental health behavior and attitudes and also their knowledge about oral and dental health care of dental students improved with increasing level of education while oral and dental health care of female students were better than males and oral and dental health care of non-smokers were better than smokers. (Eur J Dent 2009;3:24-31)
Keywords: Oral health behavior; Dental attitudes; Dental students; Turkey